PENGELOLAAN MODEL PROGRAM RADIO INTERAKTIF PADA RADIO KOMUNITAS PENDIDIKAN SMKN 1 BLITAR - Anam Miftakhul Huda; Yefi Dyan Nofa Harumike (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
Broadcast programs owned by radio mass media, interactive dialogue broadcasts are broadcast programs that are also owned by the mass media, one of which is radio broadcasts. Interactive dialogue program is a conversation that is carried out in television or radio mass media, which can involve viewers and listeners by telephone or message on social media or other communication tools so that they can interact with sources in the studio. The selected speakers are people who know exactly about the information they want to convey. This interactive radio model is truly capable of providing effective information to listeners. The method of this service activity is by giving training to students of SMK 1 Blitar namely in the direction of TP3R (Radio Program Broadcasting and Production Techniques). During the activity, participants actively follow the material and practice in an interactive dialogue. The enthusiasm of the participants in the event was able to develop the abilities of participants in radio management management by using interactive models as a form of community aspirations in the mass media. The result was that students participated in training in interactive dialogue material, lasung practice, and evaluation of interactive radio programs.